2021
DOI: 10.1111/ped.14451
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve palsy with acute otitis media associated with EB virus infection

Abstract: pediatricians should be alert to trends in KD incidence during the current pandemic of COVID-19 not only in Europe or the USA but also in East Asia.In conclusion, our patient developed KD 8 weeks after COVID-19 onset while he still had fecal viral shedding. The timeline in the present case may strengthen the hypothesis of a possible association between the two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…EBV-infected patients can exhibit a wide spectrum of clinical courses, ranging from asymptomatic to IM to malignant diseases. Cases of EBV infection presenting with otitis media preceding facial nerve palsy, as in our case, have rarely been reported in pediatric patients [10,11]. Although the underlying mechanism remains uncertain, it has been theorized that EBV, followed by a secondary bacterial infection, might be involved in developing otitis media and mastoiditis, leading to inflammation and edema within the tympanic cavity, which in turn causes facial nerve compression resulting in facial palsy [11].…”
Section: Case Reportmentioning
confidence: 67%
See 1 more Smart Citation
“…EBV-infected patients can exhibit a wide spectrum of clinical courses, ranging from asymptomatic to IM to malignant diseases. Cases of EBV infection presenting with otitis media preceding facial nerve palsy, as in our case, have rarely been reported in pediatric patients [10,11]. Although the underlying mechanism remains uncertain, it has been theorized that EBV, followed by a secondary bacterial infection, might be involved in developing otitis media and mastoiditis, leading to inflammation and edema within the tympanic cavity, which in turn causes facial nerve compression resulting in facial palsy [11].…”
Section: Case Reportmentioning
confidence: 67%
“…Additionally, corticosteroids for inflammation control and surgical drainage of pus can be considered based on the patient's condition. However, the efficacy of using the antiviral agent acyclovir as a treatment option is uncertain [10,11]. contributes to secondary HLH [13].…”
Section: Case Reportmentioning
confidence: 99%
“…Complete recovery of the facial nerve was documented in 4 patients, whereas a slight paresis occurred in one patient two years after the hospitalization. Recently, Yamaguchi et al have reported two cases of 18 and 19-month-old female children with unilateral facial nerve palsy with ipsilateral AOM and primary EBV infection [ 6 ]. They received oral corticosteroids and vitamin B12 supplementation, and both recovered after 12 and 6 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, facial nerve palsy with AOM associated with Epstein-Barr virus (EBV) infection has been rarely observed [ 5 , 6 ]. Here, we describe a case of a previously healthy male child with acute onset of AOM-related facial nerve palsy associated with recent EBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, AOM is not common; however adults have up to 10 time's greater chance of developing peripheral facial paralysis [PFP] as a complication than pediatrics [3] .…”
Section: Introductionmentioning
confidence: 99%